INFLUÊNCIA DAS TEMPERATURAS DE AUSTENITIZAÇÃO E AUSTÊMPERA NA MICROESTRUTURA E PROPRIEDADES DE TRAÇÃO DE UM FERRO FUNDIDO NODULAR - Boneti, Ludiere Lucas Toldo (2014)
The present study aimed to evaluate the influence of the austempering heat treatment parameters on microstructure and mechanical properties of a ductile cast iron produced in industrial conditions, containing 3.59% carbon, 2.68% silicon, 0.46% copper (in wt%) and a carbon equivalent of 4.50%. The material was produced in a foundry located in the southwest region of Parana state, Brazil. The specimens were obtained by casting the alloy into Y-block molds. The austempering heat treatments consisted of pre-heating at 500°C, followed by austenitizing step at 870°C, 900°C and 930°C during 60 minutes. Austempering was carried out in molten metal baths at temperatures of 300°C and 370°C for 30 minutes. Microstructural characterization was carried out by light optical microscopy (LOM) with image analysis, scanning electron microscopy (SEM-FEG) and X-ray diffraction with Rietveld refinement. The mechanical properties were evaluated by tensile and Vickers hardness tests. The as-cast microstructure displayed a very heterogeneous microstructure, characterized by the presence of regions with graphite flotation and carbide containing intercellular regions. The graphite nodules showed low nodularity, of 85%, which was attributed to the fading effect of magnesium alloy. Austempered samples were characterized by the presence of bainitic ferrite, interspersed with retained austenite in films and blocks. The austempering at 300°C resulted in a finer microstructure containing smaller volume fractions of retained austenite. All heat treated samples displayed transformation gradients between graphite flotation and intercellular regions. These gradients affected the mechanical properties, as well as the fracture characteristics. The best results of mechanical properties were obtained in the specimen austenitized at 900°C followed by austempering at 300°C, allowing the ADI produced to fit into a high strength class, according to ASTM A897. The study of fracture surfaces showed a sharp transition between graphite flotation and intercellular regions. The fracture at the vicinity of graphite nodules have occurred by a ductile mechanism, characterized by dimples. It was observed a rapid transition to the cleavage mode at intercellular regions, containing solidification carbides.